2015
DOI: 10.1080/14774003.2015.11667817
|View full text |Cite
|
Sign up to set email alerts
|

On the Move and Working Alone: Policy Implications of the Experiences of Unionised Newfoundland and Labrador Homecare Workers

Abstract: Home care work is female-dominated, generally precarious, and takes place in transient and sometimes multiple workplaces. Home care workers can engage in relatively complex employment-related geographical mobility (E-RGM) to, from, and often between work locations that can change frequently and are remote from the location of their employer. Like other precarious workers, home care workers may be more likely to experience work-related health and safety injuries and illnesses than non-precarious workers. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Substantial difficulties were also reported with most operational stressors (i.e., mean scores from 2.21 to 4.14 out of 7), such as working alone at night and fatigue associated with shift work and over-time. These types of stressors were identified as potentially problematic in previous research conducted in other occupations [69][70][71].…”
Section: Discussionmentioning
confidence: 93%
“…Substantial difficulties were also reported with most operational stressors (i.e., mean scores from 2.21 to 4.14 out of 7), such as working alone at night and fatigue associated with shift work and over-time. These types of stressors were identified as potentially problematic in previous research conducted in other occupations [69][70][71].…”
Section: Discussionmentioning
confidence: 93%
“…Our study contributes to the small body of empirical research that has addressed the relationship between precarious employment and geographical mobility (Bohle et al, 2004;Zeitinoglu et al, 2004;MacDonald, 2009;Access Alliance Multicultural Health, 2011;Wilson et al, 2011;Fitzpatrick and Neis, 2015;Premji and Shakya, 2016), and to the growing number of studies that have looked at how changes in the nature of employment is necessitating increased mobility from workers (Newhook et al, 2011;Haan et al, 2014). To our knowledge, ours is one of only two empirical studies that have specifically focused on the multiple and complex ways in which precarious employment impacts daily commutes (Fitzpatrick and Neis, 2015), and the only one to have done so in an urban context. While most Canadian studies on employment-related geographical mobility to date have focused on mobile occupations, ours brings to light the fact that non-transient occupations can have an important mobility component, not only because of where the work is located, but because of how it is organized.…”
Section: Discussion and Recommendationsmentioning
confidence: 89%
“…As MacDonald (2009) has argued, precarious employment has an inherent spatial dimension. This dimension has been highlighted, to a limited extent, in studies conducted among precariously-employed workers, which found that holding multiple jobs or working in split-shifts, at night or in varying locations, increased commuting time and transportation expenses and resulted in unsafe journeys to and from work (Bohle et al, 2004;Zeitinoglu et al, 2004;Fitzpatrick and Neis, 2015;Premji and Shakya, 2016). Dimensions of mobility have also been incorporated in conceptual models of the impacts of precarious employment.…”
mentioning
confidence: 99%
“…Scholars from across disciplines are paying increasing attention to ERGM and relevant theoretical perspectives in various sectors (Cresswell et al 2016;Green 2004;Haan et al 2014). The literature on the migration and mobility of healthcare workers both globally (for example, Kingma 2006;OECD and WHO 2010;OECD 2008) and locally (Fitzpatrick and Neis 2015) is also flourishing. These studies point to a variety of challenges and concerns arising from the ERGM of healthcare workers, ranging from braindrain, labour shortages and surpluses, and de-skilling, to the isolation and exclusion faced by foreign workers, as well as the specific vulnerabilities associated with healthcare work in the domestic sphere, as faced by home care workers.…”
Section: Résumémentioning
confidence: 99%
“…ERGM-related occupational health and safety concerns for healthcare workers arise particularly in home care. Fitzpatrick and Neis (2015) note that musculoskeletal disorders, the potential for facing violence and abuse (verbal, physical or sexual), and exposure to communicable diseases and allergens are common. They draw attention to how " [v]iolence in these workplaces is under-reported, and is often tolerated by workers when the clients have dementia" (Fitzpatrick and Neis 2015: 49).…”
Section: Workplace and Occupational Health And Safety Of Tfws In Healmentioning
confidence: 99%